2017
DOI: 10.1002/ehf2.12222
|View full text |Cite
|
Sign up to set email alerts
|

Liver fibrosis score predicts mortality in heart failure patients with preserved ejection fraction

Abstract: AimsHeart failure with preserved ejection fraction (HFpEF) has several pathophysiological aspects, including stiffness and/or congestion of multiple organs. Poor prognosis is expected in heart failure patients with liver stiffness, which has recently been assessed by non‐alcoholic fatty liver disease fibrosis score (NFS; based on aspartate aminotransferase to alanine aminotransferase ratio, platelet counts, and albumin). We aimed to investigate the impact of NFS on prognosis of HFpEF patients, with considerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 47 publications
7
103
1
Order By: Relevance
“…Our findings build on this work by demonstrating the impact of liver fibrosis on cognition in a population-based, unselected sample using a liver fibrosis score that can be calculated from routine laboratory tests and that has been validated across a wide variety of underlying liver conditions. Conceptually, our findings are consistent with a growing understanding that liver fibrosis has implications for human biology and disease, irrespective of the underlying etiology, as has been observed for cerebrovascular disease and heart disease, for example [24,25,31]. Clinically, our approach takes into account Figure 1 Flow diagram of the study population for analysis of the association between liver fibrosis and cognitive measures in older adults.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings build on this work by demonstrating the impact of liver fibrosis on cognition in a population-based, unselected sample using a liver fibrosis score that can be calculated from routine laboratory tests and that has been validated across a wide variety of underlying liver conditions. Conceptually, our findings are consistent with a growing understanding that liver fibrosis has implications for human biology and disease, irrespective of the underlying etiology, as has been observed for cerebrovascular disease and heart disease, for example [24,25,31]. Clinically, our approach takes into account Figure 1 Flow diagram of the study population for analysis of the association between liver fibrosis and cognitive measures in older adults.…”
Section: Discussionsupporting
confidence: 82%
“…We used the FIB-4 score because we previously observed that the prevalence of liver fibrosis by this score in NHANES correlates with other population-based prevalence estimates [23]. Our approach of examining liver fibrosis without consideration of the underlying etiology is consistent with other efforts to understand the role of liver fibrosis in human biology and disease [24][25][26]. The primary analysis treated the FIB-4 score as a continuous variable.…”
Section: Assessment Of Liver Fibrosismentioning
confidence: 99%
“…Our results differ somewhat to previous studies. [11][12][13][14][15][30][31][32] For example, compared with the paper by Angulo et al, 11 we found lower hazard ratios for both mortality and liver-related events and lower AUROCs for predicting the studied outcomes. This could be because differences in cohort characteristics.…”
Section: Comparison With Previous Studiescontrasting
confidence: 56%
“…Second, diagnosis of NAFLD was not included in the present study, precluding further analysis by stratifying the presence of NAFLD. However, NFS was previously shown to be associated with CVD and mortality in different population, regardless of the presence of NAFLD or not [8,15]. Third, liver biopsy was not taken in the evaluation of brosis.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has indicated that NFS is associated with coronary atherosclerosis and predicts cardiovascular events and mortality in subjects with NAFLD [12][13][14]. Further study revealed that NFS was also associated with cardiovascular mortality in different populations, including patients with heart failure or coronary artery disease and even in the general population, regardless of the presence of NAFLD [8,[13][14][15][16]. However, the relationship between NFS and CVD in type 2 diabetic subjects was rarely studied [10,17].…”
Section: Introductionmentioning
confidence: 99%